Repeated coagulation testing in children - Bidlingmaier, C.; Treutwein, J.; Olivieri, M.; Kurnik, K. (Hämostaseologie, 2011)
Background Mild bleeding disorders (BD) such as von Willebrand disease (VWD) type I are often difficult to diagnose because of inconclusive laboratory results. Our study examines the diagnostic value of repeated testing.Patients, methods Prospective study on 200 children. Extensive laboratory testing was done twice and a standardized history was taken.Results 165 patients completed the study (median age 5.6 years). Main reason for referral was aPTT prolongation (n = 109). The initial diagnosis was upheld in 74/165 (44.8%) children. Of 18 patients rated normal, 8 had to be reclassified as possible VWD later. Ten patients were diagnosed VWD I. In 36 patients possible VWD was found, 13 of these had normal results at the second visit while in 6 VWD became more likely. The main diagnosis was lupus-anticoagulant (n=79), normalizing in 24. A total of 88 children underwent surgery during the study period.Conclusion Our study shows frequent changes in the diagnosis and highlights the limitations of single laboratory tests in detecting mild BD. Clinical and laboratory abnormalities have to be followed and tests must be repeated in unclear cases. Normal values at one point do not exclude a BD.
Keywords: Coagulation screening; repeated testing; von Willebrand disease; children